A simple and excellent protocol for the synthesis of CdSe QDs sensitized SmCoO3 peroviskite nanoparticles. (2021) - Soumya Rani, D.; Meera, M.R.
Abstract: This paper describe a very mild, quick and simple protocol for the synthesis of CdSe QDs sensitized SmCoO3 peroviskite nano materials. The CdSe QDs are synthesized via hot injection method and peroviskite SmCoO3 is synthesised via hydrothermal synthesis procedure. The CdSe QDs are sensitized to SmCoO3 using mercaptopropionic acid as linker to form heterostructure. The phase purity and crystallinity of CdSe QDs and SmCoO3 are examined using X-ray diffraction analysis and the morphologies are studied using transition electron microscopy (TEM) technique. The XRD analysis of CdSe QDs reveals the high crystallinity with a cubic phase and tetragonal phase for SmCoO3 . The surface morphological observations demonstrate that SmCoO3 size in the range of 80–120 nm in size. The TEM analysis reveals single crystalline nature for the SmCoO3 nanoparticles. The optical band gap of SmCoO 3 is found to be 3.75 eV and 2.33 eV for CdSeQDs. This work discusses the significance and novelty of the usage of CdSe QDs sensitized SmCoO3 heterostructure as photo-electrocatalyst and paves pathway for newer materials development for enhanced photo-electrochemical water splitting.